Police Law Enforcement Against Illegal Drug and Medical Device Trafficking in the North Sumatra Police - Priananda, Gilang; Maysarah, Andi; Silalahi, Hardian (Tasyri' : Journal of Islamic Law, 2026)
The circulation of medicines and medical devices that do not comply with legal standards constitutes a criminal act that poses serious risks to public health and safety, economic stability, and consumer protection. In this context, the police play a strategic role in carrying out repressive, preventive, and countermeasure actions against such illegal practices. This study aims to analyze law enforcement conducted by the North Sumatra Regional Police, examine the preventive measures implemented, and identify the obstacles encountered in the enforcement process. The research employs an empirical legal method with statutory and sociological approaches. The findings indicate that law enforcement is carried out through stages of investigation, inquiry, enforcement actions, and cooperation with the National Agency of Drug and Food Control, while preventive efforts include public outreach, supervision of distribution channels, and integrated operations. The main challenges involve limited resources, the evolving patterns of crime, and low public legal awareness. Therefore, strengthening inter-agency synergy, enhancing the capacity of law enforcement officers, and encouraging active public participation are necessary to improve the effectiveness of law enforcement against the illegal circulation of medicines and medical devices.